Physiological responses of rosewoods Dalbergia cochinchinensis and D. oliveri under drought and heat stresses - Hung, Tin Hang; Gooda, Rosemary; Rizzuto, Gabriele; So, Thea; Thammavong, Bansa; Tran, Hoa Tri; Jalonen, Riina; Boshier, David; MacKay, John (2021)
Little is known about the responses of endangered Rosewood species to drought and heat stress. These stresses are expected to increase in the Greater Mekong Subregion where the species co-occur and are endemic. Our results indicate contrasting relationships in water relations, photosynthetic pigment levels, and total soluble sugars in the two species, matching their ecological niches. The results support effective regeneration and conservation of the species in degraded habitats and in the face of climate change.